A competitive review of the Power industry in Singapore: from the Yokogawa’s perspective - Sng, Yong Guan, Felix (2010)
In order to create sustained competitive advantage in the Control Automation market of the Singapore Power industry, Yokogawa needs to create a strategic fit between its external environment and internal resources. As depicted by the TOWS model, Yokogawa needs to use its strengths to improve the value of its offerings, which will mitigate the negative effect of its premium pricing on its price-performance trade-off. On top of the reliability and comprehensive functionalities of its Distribution Control System (DCS), Yokogawa needs to market its strong local capability and service capabilities. This packaging approach will help to create a differentiation between Yokogawa and its competitors and build switching costs to prevent its customers from switching over to other DCS or Programmable Logic Controller.